2014
DOI: 10.1111/cdev.12329
|View full text |Cite|
|
Sign up to set email alerts
|

Discrimination of Biomechanically Possible and Impossible Hand Movements at Birth

Abstract: The development of human body perception has long been investigated, but little is known about its early origins. This study focused on how a body part highly relevant to the human species, namely the hand, is perceived a few days after birth. Using a preferential-looking paradigm, 24- to 48-hr-old newborns watched biomechanically possible and impossible dynamic hand gestures (Experiment 1, N = 15) and static hand postures (Experiment 2, N = 15). In Experiment 1, newborns looked longer at the impossible, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 65 publications
5
24
0
Order By: Relevance
“…A preference for the possible grip would be in line with earlier demonstrations of infants' preference for familiar motion patterns, such as human biological motion (Bertenthal, Proffitt, & Cutting, ; Bertenthal et al., ; Simion et al., ), biologically possible vs. impossible whole‐body movements (Christie & Slaughter, ), and movements that are already part of infants' motor repertoire (Sanefuji, Ohgami, & Hashiya, ). Conversely, a preference for the impossible grip would suggest that the movement is perceived as an unfamiliar, unexpected event as compared to the overly familiar possible movement, and would be in accord with earlier demonstrations of longer looking times to unfamiliar body shapes and movements (Christie & Slaughter, ; Geangu et al., ; Longhi et al., ; Morita et al., ; Reid et al., ; Slaughter et al., ).…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…A preference for the possible grip would be in line with earlier demonstrations of infants' preference for familiar motion patterns, such as human biological motion (Bertenthal, Proffitt, & Cutting, ; Bertenthal et al., ; Simion et al., ), biologically possible vs. impossible whole‐body movements (Christie & Slaughter, ), and movements that are already part of infants' motor repertoire (Sanefuji, Ohgami, & Hashiya, ). Conversely, a preference for the impossible grip would suggest that the movement is perceived as an unfamiliar, unexpected event as compared to the overly familiar possible movement, and would be in accord with earlier demonstrations of longer looking times to unfamiliar body shapes and movements (Christie & Slaughter, ; Geangu et al., ; Longhi et al., ; Morita et al., ; Reid et al., ; Slaughter et al., ).…”
Section: Methodssupporting
confidence: 76%
“…In an action context, infants discriminate between possible and impossible (i.e., violating the constraints of the fingers) grasping actions at about 6 months (Geangu et al., ). Of note, when exposed to possible and impossible whole‐hand grasps, even 2‐day‐old newborns discriminate between the two (Longhi et al., ). Given that whole‐hand grasps are part of newborns' motor repertoire, these findings suggested that sensitivity to violations of hand's physical constraints during the observation of whole‐hand gestures at birth would be modulated by newborns' own sensorimotor experience with that specific grip.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Longhi and colleagues (2015) found that newborns distinguish between possible and impossible hand gestures only when hands were dynamic and not static. The authors speculated that movement provides additional information highlighting the novelty of the appearance of the impossible hand gesture compared with the possible one.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies suggested that sensitivity to body structure in static images was not apparent until the second year of life [81]. However, recent behavioral work suggests that infants may be sensitive to disruptions in the configuration of the human body at significantly younger ages [8284]. Accompanying these behavioral investigations is a small number of studies examining infant neural responses to experimentally manipulated disruptions in bodily representations in static and dynamic displays [8588].…”
Section: Figurementioning
confidence: 99%